1
$\begingroup$

Let $P(M,G)$ be a principal fiber bundle. Let $\sigma : U \subseteq M \rightarrow P$ be a smooth local section and $f : U \rightarrow G$ a smooth function. For $ a \in G$, $R_a : P \rightarrow P$ is the map $u \mapsto u \cdot a$. For $u \in P$, $L_u : G \mapsto P$ is the map $g \mapsto u \cdot g$. Now let $\sigma' = \sigma \cdot f$, $x \in U$ and $X \in T_x M$. Why is

$$ \sigma'_{*} (X) = (R_{f(x)})_{*}(\sigma_{*}(X)) + (L_{\sigma(x)})_{*}(f_{*}(X)) $$

? My book says it's because of the Leibniz rule, but I don't know of any Leibniz rule that looks like that.

$\endgroup$
3
$\begingroup$

Let $\gamma:(-\varepsilon,\varepsilon)\to M$ be an smooth curve generating $X$, i.e. $\dot{\gamma}(0)=X$. We then write $\sigma(t)$, $f(t)$ for $\sigma(\gamma(t))$, $f(\gamma(t))$ so that by definition we have $$\sigma'_*(X)=\left.\frac{d}{dt}\right|_{t=0}\mu(\sigma(t),f(t)),$$ where $\mu:P\times G\to P$ denotes the $G$-action on $P$. Using the canonical isomorphism $T_{(\sigma(x),f(x))}(P\times G)\to T_{\sigma(x)}P\oplus T_{f(x)}G$, we compute \begin{align}\left.\frac{d}{dt}\right|_{t=0}\mu(\sigma(t),f(t))&=\mu_*(\dot{\sigma}(0),\dot{f}(0))=\mu_*(\dot{\sigma}(0),0)+\mu_*(0,\dot{f}(0))\\&=\left.\frac{d}{dt}\right|_{t=0}\mu(\sigma(t),f(0))+\left.\frac{d}{dt}\right|_{t=0}\mu(\sigma(0),f(t))\\&=\left.\frac{d}{dt}\right|_{t=0}R_{f(x)}(\sigma(t))+\left.\frac{d}{dt}\right|_{t=0}L_{\sigma(x)}(f(t))\\&= (R_{f(x)})_{*}(\sigma_{*}(X)) + (L_{\sigma(x)})_{*}(f_{*}(X))\end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.